2014
DOI: 10.1002/srin.201300445
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Reaction between Iron‐Based Alloys and Polycrystalline α‐Al2O3

Abstract: The effect of temperature, atmosphere, and elemental concentrations of boron and phosphorous in ferrous alloys on the wettability of polycrystalline α‐Al2O3 was studied. The investigation of the wetting behavior is of major importance to the infiltration of steel into open foam ceramics. In reference Fe‐0.46 wt% C iron samples, the contact angle was investigated between 1550 and 1650 °C under Ar‐H2 and Ar atmospheres and was found to decrease with increasing temperature and increasing oxygen partial pressure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…The best fit of drop mass of the recorded drop shape and the calculated shape numerical solving the Young-Laplace equation is set for the SD experiments. A CCD-camera (resolution 640 9 480 pixels) constantly recorded the drop profile [23]. In the case of the MBP and the SD experiments, the argon gas is provided by a liquid gas tank (V = 3.4 m 3 , p = 32 bar) with a vaporizer unit.…”
Section: Sessile Dropmentioning
confidence: 99%
“…The best fit of drop mass of the recorded drop shape and the calculated shape numerical solving the Young-Laplace equation is set for the SD experiments. A CCD-camera (resolution 640 9 480 pixels) constantly recorded the drop profile [23]. In the case of the MBP and the SD experiments, the argon gas is provided by a liquid gas tank (V = 3.4 m 3 , p = 32 bar) with a vaporizer unit.…”
Section: Sessile Dropmentioning
confidence: 99%
“…As a possible alternative, boron was previously tested on the liquid iron. Dubberstein et al [4] have indicated reduction of the contact angle between boron-alloyed iron and alumina substrate compared to the pure iron sample.…”
Section: Introductionmentioning
confidence: 99%
“…The slag was mixed uniformly and compacted into cylindrical samples of 5 mm diameter and 5 mm height for the investigation of melting behavior in the high-temperature microscope. The high-temperature microscope detailed description and experimental procedure can be found elsewhere [36]. The experiments were carried out under argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%